1989
DOI: 10.2307/2786904
|View full text |Cite
|
Sign up to set email alerts
|

Managing Emotions in Medical School: Students' Contacts with the Living and the Dead

Abstract: Professionals are not supposed to feel desire or disgust for their clients, and they presumably begin to learn "affective neutrality" in professional school. Medical students learn to manage the inappropriate feelings they have in situations of clinical contact with the human body, but two years of participant observation revealed that the subject of "emotion management" is taboo. Yet the culture of medicine that informs teaching also includes a hidden curriculum of unspoken rules and resources for dealing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
249
0
6

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(262 citation statements)
references
References 22 publications
7
249
0
6
Order By: Relevance
“…This reflects previous findings that medical students often utilise defensive strategies to minimise anxieties arising from conducting human dissection (e.g., Abu-Hijelh et al, 1997;Charlton et al, 1994;Sanner, 1997). Smith and Kleinman (1989) noted how defensive strategies, such at overly intellectualising the process of human dissection, could allow students to become more involved in the process of learning in which they "gradually come to see the human body as an interesting object, separate from the person" (p. 65). This sentiment was reproduced by our female participant who, towards the end of her first year, articulated the construct 'a learning tool -a body'.…”
Section: Discussionmentioning
confidence: 63%
“…This reflects previous findings that medical students often utilise defensive strategies to minimise anxieties arising from conducting human dissection (e.g., Abu-Hijelh et al, 1997;Charlton et al, 1994;Sanner, 1997). Smith and Kleinman (1989) noted how defensive strategies, such at overly intellectualising the process of human dissection, could allow students to become more involved in the process of learning in which they "gradually come to see the human body as an interesting object, separate from the person" (p. 65). This sentiment was reproduced by our female participant who, towards the end of her first year, articulated the construct 'a learning tool -a body'.…”
Section: Discussionmentioning
confidence: 63%
“…Routine physical examination of patients requires a physical intimacy that could evoke strong feelings in a personal context that are regarded as unprofessional in medical practice. Smith III and Kleinman (1989) reported that as medical students encounter the human body, they experience a variety of uncomfortable feelings including embarrassment, disgust and arousal. Medical students often struggle with knowing how to deal with these feelings in their initial encounters with patients (Haas & Shaffir 1982).…”
Section: Discussionmentioning
confidence: 99%
“…This circumvents the confusion that was created in the stress and coping literature by predefining defenses as maladaptive and coping as adaptive (Parker & Endler, 1996). Thus, cognitive strategies that dampen negative emotions may permit medical professionals to operate successfully (Lief & Fox, 1963;Smith & Kleinman, 1989). The same strategies, however, may be used to dehumanize an enemy and neutralize empathic distress that could interfere with state-sanctioned killing (Bandura, 1977).…”
Section: Defining Emotion Regulationmentioning
confidence: 99%